Enabling the Grass Root: Health Cadres Empowerment Program in Efforts to Prevent and Manage Hypertension in the Tanjung Sub-Village Community - Purwanta Purwanta; Deskantari Murti Ari Sadewa; Diarannisa Sahrinanda; Indah Rizky; Ismi Marfuatim Muthoharoh; Vina Yunistyaningrum (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Community health cadres are frontline health workers and essential allies in improving hypertension management and promoting health equity. However, the phenomenon in Indonesia shows that the support given to cadres in efforts to promote hypertension still needs to be higher. This article describes the community service program, especially health cadres empowerment in Tanjung Sub-villages, Sewon, Special Region of Yogyakarta, to optimize the capabilities of health cadres in promoting health and preventing disease. The methods to determine the lack in community used observation, interviews, and surveys. Action planning was carried out by including cadres, primary health care services Sewon II, head of sub-village, village youth organization. Implementation of the program was held in May 2023. The descriptive analysis was used for analyzing the preliminary surveys. The Wilcoxon test was carried out to measure cadres’ knowledge before and after the program was held as an evaluation. There are two main programs for empowering health cadres in this community: health cadre training and hypertension exercise to increase cadres’ innovation in doing exercise for the community. Both of these programs have been proven to increase the knowledge and understanding of cadres about hypertension, as well as improve the ability of cadres to carry out health screening and lead hypertension exercises. Based on the results of the Wilcoxon test, the pre-test, and post-test values yielded a Z value of -2.375 and a sig value of 0.018, indicating that there is an influence of the presentation of hypertension on the knowledge and understanding of the cadres. Community acceptance of this program runs well and the Tanjung Sub-Village’s Cadres independently are able to carry out health screening for non-communicable diseases, especially hypertension in their monthly Integrated Healthcare Center (Posyandu) program in the future.